Influência do contexto ambiental no desempenho motor e cognitivo de crianças frequentadoras de creches - Santos, Mariana Martins dos (2013)
The first years of life are a period of constant changes in child development. The identification of risk factors that may affect the course of development is very important to avoid damage throughout the process. Among the environmental risk factors, stand out low socioeconomic status and low education level, beyond the quality of stimulation that is given to child. The child care centers is an important source of stimulus for child population. Faced with the studies reporting low quality of Brazilian's schools, this thesis aimed to investigate the influence of the school environment in motor and cognitive performance of children 0-3 years old. Looking for evidences about the influence of environmental context on motor and cognitive development of preschoolers, the Studi 1 was done by the literature review. This study allowed the identification that the quality of child care is related with the cognitive development of children in the child care centers. However a gap was identified regarding the influence of the school context in motor development. In view of this was done the Study 2, which compared the performance of motor and cognitive development of children day care centers in the same socioeconomic status. In this study it was found that the cognitive, fine motor and gross motor of children in public schools are inferior to private school children. Considering these results, the Study 3 was conducted to assess the environmental aspects of public and private kindergartens that lead to the differences found. This study confirms the importance of family characteristics such as socioeconomic status, maternal education and paternal education for child development. The quality of the school environment is related to cognitive and fine motor performance. Overall, the studies underscore the importance of quality in stimulating child development and the need for monitoring and stimulation of children attending day care centers.